Keunggulan Dan Ketangguhan Ideologi Pancasila - Surajiyo Surajiyo (Universitas Persada Indonesia YAI, 2020)
Ideology actually comes from a philosophical system, and is the implementation of aphilosophical system. Communism originated in the philosophy of materialism, gave birth toatheism and class struggle and the dictatorship of the proletariat. Pancasila originates fromthe philosophy of the Indonesian nation itself since time immemorial in the 'triprakoro'(Notonagoro term), namely customs, culture, and religion. Then with deep thought the'founding fathers' made Pancasila the state ideology. Pancasila as the ideology of theIndonesian nation is the work of the Indonesian nation itself, which is parallel to the othermajor ideologies in the world, it even has advantages over other ideologies.This research method is based on literature research, so the data collected isqualitative data that is processed by reflective method, equipped with the 'verstehen' method.The results showed that the Pancasila ideology had advantages over the ideology ofcommunism, liberalism and fascism. The Pancasila ideology also has resilience not onlybecause of the internal factors of the ideology itself, namely its amazing unanimity andintegrity, but also because of the support of external factors, namely the guardians of thePancasila ideology, both formal and informal.